Proving content validity of self-regulated learning scale (The comparison of Aiken index and expanded Gregory index) - Heri Retnawati (Program Pascasarjana Universitas Negeri Yogyakarta & HEPI, 2016)
This study aims to prove the content validity of the self-regulated learning (SRL) scale using Likert model and multiple-choice model with content validity coefficient based on expert assessments with Aiken formula and expanded Gregory formula. In this study, the SRL scale with Likert and multiple-choice model are developed using the same outline/format. There are three experts who assess the items' relevancy using indicators of both scale formats. The results of the expert assessments are then used to calculate the coefficient of the validity with Aiken formula and the expanded Gregory formula. The results showed that the content validity coefficient based on expert assessment on Likert and multiple-choice format with Aiken formula is at 0.9 for each, while using the Aiken formula and expanded Gregory formula, the coefficient is 0.6 for Likert, and 0.8 for multiple-choice.